TATA RUANG IBUKOTA TERAKHIR KERAJAAN GALUH (1371 - 1475 M) - Budimansyah Budimansyah; Nina Herlina Lubis; Miftahul Falah (Patanjala: Journal of Historical and Cultural Research, 2020)
Penelitian ini bertujuan untuk menguak tata ruang Galuh Pakwan sebagai ibukota terakhir Kerajaan Galuh, sejauhmana pola ruang kota tersebut berkaitan dengan nilai-nilai kelokalan sebagaimana tergambar dalam historiografi tradisional. Dalam penelitian ini metode sejarah akan dipergunakan sebagai fitur utama agar menghasilkan suatu hasil kajian yang komprehensif, dan menggunakan teori tata kota, serta metode deskriptif-kualitatif. Minimnya sumber terkait sejarah Galuh Pakwan, wawancara secara mendalam kepada para narasumber diharapkan bisa menjadi suatu bahan analisis historis. Berdasarkan fakta di lapangan, Galuh Pakwan sebagai ibukota kerajaan berawal dari sebuah kabuyutan. Pada masa pemerintahan Niskalawastu Kancana, kabuyutan tersebut dijadikan pusat politik dengan tetap menjalankan fungsi kabuyutannya. Seiring waktu, Galuh Pakwan menjelma menjadi sebuah kota yang tata ruangnya menunjukkan representasi dan implementasi konsep kosmologi Sunda. Galuh Pakwan terbentuk oleh pola radial-konsentris menerus, sebagai gambaran kosmologi Sunda sebagaimana terungkap dalam naskah-naksah Sunda kuna.The research is not only aimed at uncovering the spatial layout of Galuh Pakwan as the last capital of Galuh Kingdom, but also at exploring how well the relationship between the urban spatial patterns and the local values as depicted in the traditional historiography. Beside having the historical methods as the main feature to produce a comprehensive study result, the study also uses the urban planning theory, as well as the descriptive qualitative methods. The historical sources related to the history of the Galuh Pakuan are very limited. As a result, the in-depth interviews with the resource persons are expected to be appropriate as the observation material for historical analysis. Based on the facts found in the field, the Galuh Pakwan as the capital of the kingdom originated from a Kabuyutan. During the reign of Niskalawastu Kancana, Kabuyutan served as a political center while maintaining its original function as Kabuyutan. As the time passed, the Galuh Pakwan was transformed into a city whose spatial layout represented and implemented the Sundanese cosmological concept. The Galuh Pakwan was formed by a continuous radial-concentric pattern, as a description of Sundanese cosmology in the ancient Sundanese manuscript.